THU0286 Recurrence of arterial and venous thromboses in primary antiphospholipid syndrome. (15th June 2017) - Balbi, G; Signorelli, F; Levy, RA
Abstract : Background: Antiphospholipid syndrome (APS) is the thrombophilia associated with the highest risk of recurrence of both arterial and venous thromboses. (1, 2) In addition to the standard of care (lifelong oral anticoagulation), identification of other risk factors is important to provide better care and to reduce the incidence of rethrombosis. Objectives: To investigate the risk factors associated with recurrence of arterial and venous thromboses in primary APS patients. Methods: A cross-sectional study was performed in a group of 80 outpatients who fulfilled APS classification criteria (Sydney). The patients were regularly seen in our department, and clinical and serological features were collected during visits and by chart review. They were classified as recurrent or not, and these groups were compared. Recurrence was defined as the presence of 2 or more thrombotic events during lifetime. Patients with 1 thrombotic event were classified as "no recurrent". No history of thrombosis was the only exclusion criteria. Results: Of 80 pAPS patients, thirty-five had arterial thrombosis and 54 had venous thrombosis. Of them, thirty-six had recurrent thromboses (11 arterial and 25 venous). Demographic and clinical characteristics of the arterial group are shown in Table 1 . In a bivariate analysis, recurrent arterial thromboses were associated with hypertension (p=0.016) and positivity to lupus anticoagulant (LA; p=0.033), and recurrent venous thrombosis correlated to obesity (BMI≥30 kg/m 2 ; p=0.003). In a multivariate regression analysis, the model of recurrent arterial thromboses was adjusted to age, sex, and variables with p<0.10 in the bivariate analysis (age, hypertension, dyslipidemia, and positivity to lupus anticoagulant). Hypertension (OR 9.02; CI95% 1.05–77.5; p=0.045) and age (OR 1.16; CI95% 1.01–1.33; p=0.035) increased the risk of relapse of arterial thrombosis. Conclusions: This data suggests that hypertension, a traditional cardiovascular risk factor, is associated with increased risk of recurrent thrombosis and, therefore, should be controlled in pAPS patients. Besides, each additional year of age is associated with the risk of 16% of a new arterial thrombotic event. References: R. Cervera, M.A. Khamashta, Y. Shoenfeld, et al., Morbidity and mortality in the antiphospholipid syndrome during a 5-year period: a multicentre prospective study of 1000 patients, Ann. Rheum. Dis. 68 (2009) 1428–1432. M. Turiel, P. Sarzi-Puttini, R. Peretti, et al., Thrombotic risk factors in primary antiphospholipid syndrome: a 5-year prospective study, Stroke 36 (2005) 1490–1494. Disclosure of Interest: None declared